2022
DOI: 10.3389/fendo.2022.1001316
|View full text |Cite
|
Sign up to set email alerts
|

The potential impacts of circadian rhythm disturbances on male fertility

Abstract: A circadian rhythm is an internalized timing system that synchronizes the cellular, behavioral, and physiological processes of organisms to the Earth’s rotation. Because all physiological activities occur at a specific time, circadian rhythm disturbances can lead to various pathological disorders and diseases. Growing evidence has shown that the circadian clock is tightly connected to male fertility, and circadian perturbations contribute to infertility. The night shiftwork, insufficient sleep, and poor sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 113 publications
(268 reference statements)
1
7
0
Order By: Relevance
“…These hormones are required for reproductive health through the production of testosterone and spermiogenesis in males and ovulation, embryo implantation, and follicular health in females ( 89 91 ). Though more frequently studied in females, current studies suggest that severe circadian disruption, through changes either in light exposure or via direct disruption to the SCN, may have a mild influence on male fertility ( 92 ). Interestingly, we found that Vax1 Vip males had delayed pubertal onset.…”
Section: Discussionmentioning
confidence: 97%
“…These hormones are required for reproductive health through the production of testosterone and spermiogenesis in males and ovulation, embryo implantation, and follicular health in females ( 89 91 ). Though more frequently studied in females, current studies suggest that severe circadian disruption, through changes either in light exposure or via direct disruption to the SCN, may have a mild influence on male fertility ( 92 ). Interestingly, we found that Vax1 Vip males had delayed pubertal onset.…”
Section: Discussionmentioning
confidence: 97%
“…Active training time and calories burned per day have been both increased by 50%, while sleeping pattern was increased by 20%. Unfortunately, there are not enough clinical studies and evidence that any of these parameters have positive influence on sperm quality 5,19,20 …”
Section: Discussionmentioning
confidence: 99%
“…He is in the age of 44, which could be already critical for quality of sperm according to Jimbo et al 10 However, taking under consideration all medical exams done, as well as body shape and physical activities (Figure 1), patient had very healthy lifestyle and was in a good condition. In addition to medication, patient worked on addictive habits (smoking, drinking, drugs and medication use, alcohol), 4 sleep pattern, 5 daily sport activities, 19,20 stress level, 3 coffee consumption, 3 food quality, 6 and antioxidants use. 17,18,21,22 Since patient does not smoke or use drugs, only two habits that he changed in this period are reducing alcohol consumption 4-5 drinks per week to 1-2 maximum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 5 6 7 This is called circadian rhythm 4 5 6 7 which is essential to maintain physiological functions and guarantee optimal performance for organisms. 6 7 At molecular level for circadian system, 8 9 the circadian locomotor output cycles kaput (CLOCK) and brain/muscle aryl-hydrocarbon receptor nuclear translocator-like protein 1 (BMAL1) polymerize the positive complex to activate transcription of other clock genes (such as period 1/2/3 [ PER1/2/3 ], cryptochrome 1/2 [ CRY1/2 ], retinoic acid-related orphan nuclear receptor [ REV-ERB ], and retinoic acid-related orphan receptor [ ROR ]) and clock-controlled genes. 10 11 PER and CRY accumulate in the cytoplasm and translocate to the nucleus to restrict the activity of CLOCK/BMAL1, forming the main negative feedback loop.…”
Section: Introductionmentioning
confidence: 99%